Pohádka o chudém chlapci, který ke štěstí přišel, aneb „Kapitalistický vykořisťovatel“ František Křižík v marxistické historiografii a publicistice - Eva Mušková (Theatrum Historiae)
František Křižík is one of the few technicians in the Czech history who is perceived as a national hero. This study deals with the notion of his personality as a “capitalistic entrepreneur” as interpreted by Marxistic society in the fifties of the 20th century.